Diagnosis and Monitoring of Choroidal Osteoma through Multimodal Imaging. (8th September 2014) - Empeslidis, Theodoros; Imrani, Usman; Konidaris, Vasileios; Mushtaq, Fizza; Fotiou, Pandelis; Kumar, Periyasami; Banerjee, Somnath; Tsaousis, Konstantinos T.
Abstract : A 16-year-old Caucasian female with a 6-month history of decreased visual acuity and metamorphopsia in the left eye is reported. The fundus of the left eye revealed a well defined lesion in the macula region. Diagnosis of choroidal osteoma was established using spectral domain optical coherence tomography (OCT), fundus fluorescein angiography (FFA), indocyanine green angiography (ICG), and B-scan ultrasonography. Subretinal fluid (SRF) and retinal pigment epithelium (RPE) detachment were noted in the absence of obvious classic choroidal neovascularisation (CNV). The patient was followed up for over 13 months without any treatment in the interim and the lesion was noted to have enlarged but visual acuity and SRF had remained stable. We report an interesting case where subretinal fluid was noted in the absence of evident choroidal neovascularisation and provide an example of the imaging modalities application in the era of "optical biopsy."